Modeling of an ion channel in its open conformation. - Domene, C; Doyle, D; Vénien-Bryan, C (2005)
We have modeled the structure of KirBac1.1 in an open state using as a starting point the structure of KirBac1.1 in its closed conformation (Protein Data Bank 1P7B). To test the validity of the open-state model, molecular dynamics simulations in octane, a lipid bilayer mimetic, were carried out. Simulations of the closed conformer were used for comparison purposes. The total simulation time was approximately 138 ns. The initial open model was refined by using projection maps obtained from electron microscopy experiments on two-dimensional crystals of the inwardly rectifying K+ channel KirBac3.1 from Magentospirillum magnetotacticum captured in its open state (C. Vénien-Bryan, unpublished data). Significant movements of the outer helices take place in going from the closed to the open model in agreement with structural and biochemical data in potassium channels, which suggests that gating is accomplished by a conformational change that takes place in the transmembrane domain upon an external stimulus. The motion of the inner helices is mainly achieved by bending at conserved glycine residues that have been previously reported to act as molecular hinges. Overall, these simulations suggest that the open conformer is stable, providing a plausible all-atom model that will enable the study of potential gating mechanisms in more detail.